SUSTENTABILIDADE ORGANIZACIONAL E ECOINOVAÇÃO NA PRODUÇÃO DE FÓSFOROS ECOLÓGICOS - Velozo, Ana Carolina (2018)
This study was developed based on the concept of eco-innovation, in which innovation refers to the elaboration of new products, processes and services carried out with a view to meeting the needs and improving the quality of life, without, however, threatening and degrading the environment and natural resources through toxic emissions. From this perspective, the link between eco-innovation and green production is clear, with its focus on the formulation of products that, when compared to conventional ones, provide less negative consequences to nature. Thus, this research focuses on the production of green phosphors as an eco-innovation form, in which stands out the importance of considering eco-efficiency, which is a tool geared to both eco-innovation and organizational sustainability, is also highlighted. The overall objective of the study is to understand, from the concept of eco-innovation, the process of producing green matches, and the achievement of the pillars of organizational sustainability in the Alpha company. The methodology was based on the qualitative approach, through the research strategy of a case study and a descriptive method. As a data collection instrument, semi-structured interviews were carried out with the general director, two managers and five employees, field diary and direct observation in the productive sector. The data analysis was based on the content analysis, performing the triangulation of the data, through categories of analysis. The results showed that the production of green phosphors is actually the result of an eco-innovation, since innovation happened, was elaborated by improving the quality of the product and reducing the toxic emissions, both for health and for the environment. In addition, it was found that the productive system of the company can be considered ecoefficient, since the great majority of the dimensions of eco-efficiency are realized, although sometimes, unintentionally. The company also carries out other social activities, although it has not reached the level of social and environmental justice, since no actions were found that go beyond those required by the regulations. The contribution of the company to the socioeconomic insertion was not clear because data were not available that demonstrated the economic equality of those involved. However, the economic effectiveness of eco-innovation was evidenced, which brought stability to the company's production and sales. Finally, through the research, it was possible to understand that the environmental viability is the one that has more prominence in the company, including the organization policies.